The Application of The Fairness Principle Legal Protection For Parties in Limited Liability Company - Suci desy Mitalina; Sayid Muhammad Rifki Noval; Petra Bunawan (Magister Kenotariatan Universitas Pasundan, 2026)
A corporate merger is a process by which two or more legal entities are combined to form a single, larger entity. In Indonesia, the merger process is regulated under Law No. 40 of 2007 on Limited Liability Companies (Undang-Undang Perseroan Terbatas, UUPT). This article analyses the application of legal protection for the parties involved in the merger of a Limited Liability Company (Perseroan Terbatas, PT), particularly from the perspective of the fairness principle, which constitutes the principal foundation of any business transaction. Legal protection in a merger context is critical because such transactions may adversely affect certain parties, especially minority shareholders and creditors. The application of the fairness principle in PT mergers is therefore essential to the creation of a fair and transparent business climate. Using a descriptive-qualitative method with a normative juridical approach, the study examines the relevant Indonesian statutory framework alongside scholarly commentary on corporate fairness. The findings indicate that, although the UUPT and its implementing regulations have established a multi-layered framework of protection covering shareholders, creditors, and workers, gaps remain in the operationalisation of fairness, particularly in the areas of transparency of information, valuation, and the protection of minority shareholders. Strengthened due diligence, independent valuation, and effective dispute resolution channels are accordingly recommended to give substantive effect to the fairness principle in Indonesian merger practice.